2014
DOI: 10.5114/pwki.2014.41460
|View full text |Cite
|
Sign up to set email alerts
|

The role of insulin-like growth factor-1 in development of coronary no-reflow and severity of coronary artery disease in patients with acute myocardial infarction

Abstract: IntroductionInsulin-like growth factor-1 (IGF-1) has atheroprotective effects via reduction in oxidative stress, cellular apoptosis, pro-inflammatory signaling, and endothelial dysfunction.AimWe hypothesized that low levels of IGF-1 may be associated with the severity and extent of coronary artery disease and development of the coronary no-reflow phenomenon in patients with acute ST-elevation myocardial infarction (STEMI) and investigated the role of the IGF-1 molecule in the coronary no-reflow phenomenon and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
2
1
Order By: Relevance
“…also reported that IGF-1 may be associated with increased fibrinogen, plasminogen activator inhibitor-1, and decreased protein S and tissue factor pathway inhibitor in acromegalic patients, which may represent a potential hypercoagulable and hypofibrinolytic state [ 40 ]. However, our results in a previous study did not show any significant association between IGF-1 levels and the development of no-reflow phenomenon in patients undergoing primary PCI for AMI [ 41 ], which may be related to the time for the measurement of IGF-1 because the level of IGF-1 may be affected by acute conditions such as inflammation [ 14 ]. Thus, IGF-1 measurement at the time of acute event may reveal uninterpretable and conflicting results.…”
Section: Discussioncontrasting
confidence: 66%
“…also reported that IGF-1 may be associated with increased fibrinogen, plasminogen activator inhibitor-1, and decreased protein S and tissue factor pathway inhibitor in acromegalic patients, which may represent a potential hypercoagulable and hypofibrinolytic state [ 40 ]. However, our results in a previous study did not show any significant association between IGF-1 levels and the development of no-reflow phenomenon in patients undergoing primary PCI for AMI [ 41 ], which may be related to the time for the measurement of IGF-1 because the level of IGF-1 may be affected by acute conditions such as inflammation [ 14 ]. Thus, IGF-1 measurement at the time of acute event may reveal uninterpretable and conflicting results.…”
Section: Discussioncontrasting
confidence: 66%
“…Insulin-like growth factor-1 (IGF-1) and the IGF-1 receptor affect the differentiation and apoptosis of various cells (16,17). IGF-1 levels decrease during aging and are decreased in patients with CVD (18,19). A low level of IGF-1 has been identified as an independent risk factor for CVD (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of IGF are reflected via autocrine, paracrine, and endocrine routes and its regulation involves complex mechanisms. IGF-1 is transported in the blood circulation by carrier proteins that are known as IGF binding proteins (IGFBPs) (1)(2)(3)(4)(5). IGF-1 has a key role in the proliferation, modification of cells in many tissues, including the myocardium, as well as in inhibition of cell necrosis and apoptosis.…”
Section: Introductionmentioning
confidence: 99%